FROZEN-WEIGHT-DRAINED-WEIGHT RELATIONSHIP IN BLOCK-FROZEN SHRIMP - Rao, K Krishna; Iyer, T S Gopalakrishna (Indian Journal of Fisheries, 2011)
The nature of relationship between drained weight and frozen weight in block-frozen shrimp wns studied with particular reference to the peeled and undeveined shrimp of small size grades. Nine sets of data were used, and regressions were determined with frozen weight as independent variate and drained weight as the dependent one. The slopes and intercepts of the nine regression lines were tested for equality. While the slopes could be considered to be uniform, the intercepts showed nonuniformity